Career Development at PT PLN (Persero) UP3 Nias - Bambang Pramono; Hilfan Helmy; Anton Sobirin; Ardani Putra Yudha; Kholilul Kholik (Yayasan Multidimensi Kreatif, 2026)
Career development is a strategic aspect of human resource management that plays an important role in improving employee competence, motivation, and performance. Organizations with effective career development systems are able to create more competent employees and strengthen employee commitment toward organizational goals. This study aims to analyze the effect of career development on employee performance at PT PLN (Persero) UP3 Nias. This research employed a quantitative approach with an explanatory research design. The population consisted of all employees of PT PLN (Persero) UP3 Nias, with a total sample of 56 respondents selected using a total sampling technique. Data were collected through a questionnaire using a five-point Likert scale consisting of 25 statement items. Data analysis was conducted using SPSS through validity testing, reliability testing, descriptive statistical analysis, linear regression analysis, t-test, and coefficient of determination analysis. The results indicate that career development is perceived at a high level with an average score of 4.16. The research instrument was proven valid and reliable with a Cronbach's Alpha value of 0.921. The regression analysis shows that career development has a positive and significant effect on employee performance, indicated by a significance value of 0.000 < 0.05 and a coefficient of determination of 46.8%. The findings demonstrate that better career development practices implemented by the organization contribute to higher employee performance. This study provides managerial implications for PT PLN (Persero) UP3 Nias to strengthen career planning systems, improve competency development programs, and establish transparent competency-based promotion mechanisms.